2021
DOI: 10.22201/icat.24486736e.2021.19.2.1582
|View full text |Cite
|
Sign up to set email alerts
|

Energy optimization by green sensing methodology for channel design in a cognitive radio network

Abstract: An inventive innovation for access of underutilized spectrum and unused range is cognitive radio (CR). Spectrum sensing is the capacity of a gadget to effectively detect the environment and to extricate data from utilizing its radio. A CR framework utilizing hypothesis testing channel banks and the enhancement of the range detecting limit for the predefined requirements on probabilities of missed discovery and of the false alert are proposed to optimize the energy in the system. The limit is additionally upgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Lastly, they concluded that (i) appropriate green and advertising policies improve the environmental and profitable goals, and (ii) their model's obtained result outperforms the same model without considering the robust optimization method. Extra works (Goyal & Gupta, 1989;Hoque & Goyal, 2006;Sarmah et al, 2006;Tseng et al, 2014;Zhang et al, 2016;Abushaega et al, 2021;Çömez-Dolgan et al, 2021;Khan et al, 2021;Perarasi et al, 2021;Pichka et al, 2022;Karimpoor et al, 2023) discovered the influence of various product-shipping policies on optimizing the global firms' internal or coordinated supply-chain systems.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, they concluded that (i) appropriate green and advertising policies improve the environmental and profitable goals, and (ii) their model's obtained result outperforms the same model without considering the robust optimization method. Extra works (Goyal & Gupta, 1989;Hoque & Goyal, 2006;Sarmah et al, 2006;Tseng et al, 2014;Zhang et al, 2016;Abushaega et al, 2021;Çömez-Dolgan et al, 2021;Khan et al, 2021;Perarasi et al, 2021;Pichka et al, 2022;Karimpoor et al, 2023) discovered the influence of various product-shipping policies on optimizing the global firms' internal or coordinated supply-chain systems.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical illustrations supported their proposals and solution methods. Extra works (Abdelall et al, 2020;Dewi et al, 2021;Di Nardo et al, 2021;Okfalisa et al, 2021;Perarasi et al, 2021;Suroso et al, 2021;Allaham and Dalalah, 2022;Lin et al, 2022) addressed the influence of various imperfection in fabrication processes on the manufacturing systems and production planning and control. Inspired by the urgent need to assist today's manufacturing firms in making cost-effective and efficient multi-item production decisions, this study develops a model to serve this purpose.…”
Section: Introductionmentioning
confidence: 99%